2022
DOI: 10.1002/smll.202202037
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Supporting Carbon Nanofibers with Ni‐Single‐Atoms and Uniformly Dispersed Ni‐Nanoparticles as Scalable Multifunctional Hosts for High Energy Density Lithium‐Sulfur Batteries

Abstract: The energy density of lithium‐sulfur batteries (LSBs) is currently hampered by modest sulfur loadings and high electrolyte/sulfur ratios (E/S). These limitations can potentially be overcome using easy‐to‐infiltrate sulfur hosts with high catalytic materials. However, catalytic materials in such hosts are very susceptible to agglomeration due to the lack of efficient confinement in easy‐to‐infiltrate structures. Herein, using carbon dots as an aggregation limiting agent, the successful fabrication of self‐suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…Therefore, this strategy shows great potential for application. Figure b shows the comparison of the rate performance of this work and other works. The adsorption energy and charge density of Li 2 S 6 on the Co/Mn-GC@N–C surface are calculated to further verify the adsorption effect of the material on lithium polysulfide. Figure c shows the charge density of the Co/Mn-GC@NC surface when combined with Li 2 S 6 , where the cyan part and yellow part represent electron loss and gain, respectively.…”
Section: Resultsmentioning
confidence: 89%
“…Therefore, this strategy shows great potential for application. Figure b shows the comparison of the rate performance of this work and other works. The adsorption energy and charge density of Li 2 S 6 on the Co/Mn-GC@N–C surface are calculated to further verify the adsorption effect of the material on lithium polysulfide. Figure c shows the charge density of the Co/Mn-GC@NC surface when combined with Li 2 S 6 , where the cyan part and yellow part represent electron loss and gain, respectively.…”
Section: Resultsmentioning
confidence: 89%
“…This phenomenon may be due to the dual-anchoring effect of g-C 3 N 4 and graphene oxide for Co 2+ ions in the preparation of a precursor, effectively preventing the aggregation of Co-species in the calcination process. These ultra-small Co-based species can significantly catalyze the polysulfide conversion due to their high surface energy and more active terminations [ 30 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, recent studies have demonstrated that tailoring metal compounds to an ultra-small size, such as nanocrystals, nanodots, and clusters, and even to the single-atomic scale could generate strong adsorption and excellent catalytic activity for polysulfides, owing to enhanced surface energy and more active terminations [ 16 , 29 , 30 , 31 ]. However, it is a great challenge to fabricate highly dispersed ultrafine metal compounds because the isolated ultra-small particles with high surface energy can susceptibly agglomerate into big particles in the synthesis process.…”
Section: Introductionmentioning
confidence: 99%
“…A representative structural model of graphene fibers (GFs) from macroscale to atomic scale is shown in Fig. 6(a) [74]. Various methods to prepare GFs mainly include electrospinning, hydrothermal self-assembly, CVD, and so on.…”
Section: D Fiber Structurementioning
confidence: 99%